Report from IJCAI 2019 – Top AI conference for 50 years Subtitle: Which Crisis is Coming First – of AI or of World Economy? (Informatica, 2019)
Abstract: Traditionally, Informatica editorial in Autumn is devoted to IJCAI, the best overall AI conference. Since in 2019 it is also the 50th anniversary of the IJCAI, it is especially interesting to overview the current and future directions. Indeed, AI is progressing fast and strong and is so interbreed with our everyday life that most of us are not even aware of. Most important, AI remains the frontrunner of our civilization and might be one of our best hopes for further human prosperity.